PENGARUH NET PROFIT MARGIN, PROFIT GROWTH DAN WORKING CAPITAL TURNOVER TERHADAP HARGA SAHAM PADA PERUSAHAAN OTOMOTIF DAN KOMPONENNYA YANG TERDAFTAR DI BEI PERIODE 2020-2022 - Purba, Imelda Rimenda; Mahendra, A.; Shalini, Witya (UNIKA Santo Thomas, 2024)
The aim of this research is to obtain empirical evidence of the influence of the variables Net Profit Margin (NPM), Profit Growth, and Working Capital Turnover (WCT) on stock prices in automotive companies and their components in the 2020-2022 period. This type of research is quantitative research. The data used in this research is secondary data. The population in this study includes all automotive companies and their components listed on the IDX in the 2020-2022 period. The sample in this study was 13 companies that met the criteria. The sampling technique in this research used purposive sampling. The data analysis used to test the hypothesis is multiple regression with a significance level of 5% and using SPSS version 23 tools. The results of this study show that the variables Net Profit Margin (NPM), Profit Growth, and Working Capital Turnover (WCT) have a partial influence to Stock Prices. Net Profit Margin (NPM), Profit Growth, and Working Capital Turnover (WCT) simultaneously influence stock prices.